Effects of a future warmer ocean on the coexisting copepods Calanus finmarchicus and C. glacialis in Disko Bay, western Greenland - Kjellerup, Sanne; Dünweber, Michael; Swalethorp, Rasmus; Nielsen, Torkel Gissel; Moller, Eva Friis; Markager, Stiig; Hansen, Benni Winding (Marine Ecology Progress Series, 2012)
The effects of temperature and food was examined for Calanus finmarchicus and C. glacialis during 3 phases of the phytoplankton spring bloom in Disko Bay, western Greenland. The 2 species were collected during pre-bloom, bloom, and post-bloom and exposed to temperatures from 0 to 10°C, combined with deficient or excess food. Fecal pellet and egg production were measured as indices for grazing and secondary production, respectively. Furthermore, changes in body carbon, nitrogen, and lipid content were measured. C. glacialis sampled before the bloom and incubated with excess food exhibited high specific egg production at temperatures between 0 and 2.5°C. Higher temperatures did not increase egg production considerably, whereas egg production for C. finmarchicus more than tripled between 2.5 and 5°C. Starved C. glacialis produced eggs at all temperatures stimulated by increasing temperatures, whereas starved C. finmarchicus needed temperatures above 5°C to produce eggs fueled by their lipid stores. Few C. finmarchicus had mature gonads at the initiation of the pre-bloom and bloom experiment, and egg production of C. finmarchicus therefore only increased as the ratio of individuals with mature gonads increased. During the bloom, both C. glacialis and C. finmarchicus used the high food availability for egg production, while refueling or exhausting their lipid stores, respectively. Finally, during the post-bloom experiment, production was low by C. finmarchicus, whereas C. glacialis had terminated production. Our results suggest that a future warmer ocean will reduce the advantage of early spawning by C. glacialis and that C. finmarchicus will become increasingly prevalent.